Effect Of Crop Rotation On Leaf Spot And Leaf Blotch Disease And Yield Of Turmeric (Journal of Plant Disease Sciences, 2018)
Turmeric (Curcuma longa) is a tropical crop grown in India, occupies the third position in its importance among spice crops and native to tropical South East Asia. The economic importance of turmeric is the dried rhizome. India has a 232.6 thousands ha area under turmeric cultivation with total production of 1189.90 thousand tons and productivity is 51.15q/ha (Anonymous 2014)). Turmeric crop is highly prone to several fungal diseases (Purthi, 2000). The serious foliar diseases reported in Uttar Pradesh are leaf spot caused by Colletotrichum capsici (Syd.) Butler & Bisby, and leaf blotch caused by Taphrina maculans, Butler. Crop rotation implies repeated sowing of the same crop in the cycle at periodical intervals because monoculture are not economically profitable to the farmers, it is due to same crop grown continuously in the same land becomes sick and unsuitable for cultivation. To overcome these problems, the work was planned to study the effect of crop rotation on management of soil borne diseases, growth and yield of turmeric.
Keywords: Turmeric; soil borne disease; crop rotation and yield